Wisata Swadaya Desa Berbasis Masyarakat dalam Meningkatkan Kelestarian Lingkungan dan Ekonomi Masyarakat Studi Kasus di Kelurahan Loloan Timur Kecamatan Jembrana, Bali - Fathurrahim (Fakultas Dakwah IAIN Jember, 2020)
In 2020 the Ministry of Environment and Forestry released the management report of 36,725,828.83 tons of waste. In Bali, especially at Kuta beach, the joint team cleaned up about 30 tons of garbage on January 1, 2021. Naturally, such condition is very concerning. However, it does not only occur on Kuta beach, but also on beaches and surrounding rivers located in Bali Province. Therefore, there is an emerging environmental movement of young people in East Loloan who call themselves DARLING or which stands for